The Corded Ware culture in the Eastern Baltic: New evidence on chronology, diet, beaker, bone and flint tool function. (October 2018) - Piličiauskas, Gytis; Asheichyk, Vitali; Osipowicz, Grzegorz; Skipitytė, Raminta; Varul, Liivi; Kozakaitė, Justina; Kryvaltsevich, Mikоla; Vaitovich, Aliaksandra; Lakiza, Vadzim; Šapolaitė, Justina; Ežerinskis, Žilvinas; Pamazanau, Mikalai; et al.
Abstract: Around 2900–2300 cal BCE, mobile stockbreeders introduced the Neolithic Corded Ware culture (CWC) into the Eastern Baltic. Here, a Central or Northern European Neolithic economy and ideology took hold despite differences in burial practices. Although around 90 CWC graves are known in the region their contents have not been intensively studied. Here, we present new AMS radiocarbon ( 14 C) measurements and carbon and nitrogen stable isotope data obtained on human bone collagen, molecular and isotopic data obtained from ceramic beakers, and user-wear data of flint and bone tools from several CWC graves, Benaičiai, Biržai, Krasnasieĺski, Dakudava 5, and Drazdy 12, in Lithuania and Western Belarus. The bone collagen δ 13 C and δ 15 N stable isotope data are rather homogenous and demonstrate that the majority of consumed protein was derived from terrestrial resources. Organic residue analysis of two CWC beakers yielded lipids consistent with ruminant carcass and dairy fats, whilst use-wear analyses indicates that bone pins, flint blades and axes were used as grinders, functional tools or had been carefully renewed before deposition respectively. Highlights: Human remains, ceramic beakers and flint and bone tools from CWC inhumations were analysed. Carbon and nitrogen stable isotope analyses indicate the consumption of terrestrial derived protein. Organic residue analyses of ceramics demonstrate that milk and ruminant adipose had been stored/processed. Use-wear analyses of bone and flint grave goods indicate they were used as grinders and for processing meat.